Psychological Features Of Uncertainty In War Conditions - Victoriia Overchuk; Nataliia Schell; Oksana Solovei-Lagoda; Nataliia Korolova; Lada Mazai; Anzhela Gelbak (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article addresses the relevant contemporary topic of uncertainty. The psychological characteristics of the category of uncertainty in wartime and life in general are identified. These include novelty, contradiction, complexity; variability of possibilities, choices, and decisions; unpredictability—the inability to forecast developments, unknowns, probabilities of events, and the absence of cause-and-effect relationships; uncontrollability—the subjective impossibility of managing the development of events, resisting surprises, predicting them, or controlling other people or circumstances. The situation of uncertainty is examined both as a threat and danger, and as an opportunity for further development and realization of one's potential. The concept of tolerance for uncertainty is revealed as a personality trait that helps individuals adapt and accept it. The characteristics of a tolerance-for-uncertainty personality are discussed, including the ability to see new opportunities in a constantly changing world, viewing challenges as tests of one's strength, enduring and accepting the nervous tension accompanying uncertain situations, and the ability to accept the unknown, new, and unusual as a stimulus for seeking new strategies, methods, and approaches in altered circumstances. Recommendations are developed for individuals in uncertain situations during wartime, aimed at planning their lives amid uncertainty and accepting and living through it. Priority tasks for individuals in uncertain conditions are identified as the rejection of the illusion of stability, belief in their strengths and capabilities, a positive attitude toward uncertainty, and readiness for change in unpredictable, volatile situations.